Scientific Evidence of the Beneficial Effects of Tomato Products on Cardiovascular Disease and Platelet Aggregation - Cámara, Montaña; Fernández-Ruiz, Virginia; Sánchez-Mata, María-Cortes; Cámara, Rosa M.; Domínguez, Laura; Sesso, Howard D. (Frontiers in Nutrition, 2022)
Cardiovascular disease (CVD) includes a group of disorders of the heart and blood vessels that includes numerous problems, many of which are related to the process called atherosclerosis. The present work is aimed to analyze the most relevant studies examining the potentially beneficial effects of tomato products on both CVD prevention and antiplatelet aggregation as well as an EFSA health claims evaluation on tomato and tomato products. To date, only one health claim has been approved for a concentrated extract of tomato soluble in water (WSTC) marketed under the patented name of Fruitflow® with two forms of presentation: WSTC I and II, with the following claim “helping to maintain normal platelet aggregation, which contributes to healthy blood flow”. Other studies also demonstrate similar beneficial effects for fresh tomatoes, tomato products and tomato pomace extracts.